2015
DOI: 10.1177/1526602815588274
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Viabahn in the Treatment of Superficial Femoral Artery Occlusive Disease

Abstract: Current evidence suggests that the Viabahn stent-graft is a safe and effective option for symptomatic SFA lesions. Prospective multicenter randomized controlled trials with long-term follow-up are needed to confirm the sustained efficacy of the Viabahn device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…Accordingly, a significantly higher 1-year primary patency rate was observed in the DCB reinforcement group. The patients without DCB reinforcement had 1-year primary and secondary patency estimates (76.4% and 88.9%, respectively) that were comparable to those published in a recent review article (58% to 80% and 57% to 93.4%, respectively) 5 as well as the Viabahn 25-cm trial for long SFA lesions. 19 Thus, DCB reinforcement at the edge can significantly improve the outcome of SFA treatment with the Viabahn stent-graft.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Accordingly, a significantly higher 1-year primary patency rate was observed in the DCB reinforcement group. The patients without DCB reinforcement had 1-year primary and secondary patency estimates (76.4% and 88.9%, respectively) that were comparable to those published in a recent review article (58% to 80% and 57% to 93.4%, respectively) 5 as well as the Viabahn 25-cm trial for long SFA lesions. 19 Thus, DCB reinforcement at the edge can significantly improve the outcome of SFA treatment with the Viabahn stent-graft.…”
Section: Discussionsupporting
confidence: 77%
“…Gore & Associates, Flagstaff, AZ, USA) has been shown to have better patency rates and long-term outcomes than bare metal stents (BMS) or balloon angioplasty for long superficial femoral artery (SFA) occlusive disease [TransAtlantic Inter-Society Consensus II (TASC) C and D]. [1][2][3][4][5][6] These advantages of the Viabahn stem from the ability of the polytetrafluoroethylene covering to prevent ingrowth of neointimal hyperplasia, which is the largest disadvantage of BMS in long SFA occlusive disease. [7][8][9][10] However, neointimal hyperplasia does occur at the edges of a Viabahn, causing edge stenosis that results in lumen thrombosis, which accounts for the majority of Viabahn failures.…”
Section: Introductionmentioning
confidence: 99%
“…4 Furthermore, no detrimental impact of stent graft placement on mortality was found in this study, 11 which is conclusive with a recent meta-analysis showing that the Viabahn stent graft is a safe and effective option for symptomatic superior femoral artery lesions. 23 In our cohort, angiographic assessment after a median follow-up of 345 days revealed only one patient with moderate, asymptomatic instent-stenosis (1.0%). In addition, we could not identify any patient with stent fracture, which goes along with excellent clinical data for nitinol self-expanding stents in femoral disease.…”
Section: Stent Graft Placement For Asarvimentioning
confidence: 99%
“…Most studies in literature are related with commonly used covered stent-graft deployment for peripheral steno-occlusive diseases. Zhang et al 11 reported 67% primary patency rate for PTFE-covered self-expandable stent-graft at three years, Speziale et al 16 reported 73.6% primary patency rate with a mean follow-up of 37.4 AE 29.3 months, Saxon et al 15 found it to be 73% at 12 months, and Lammer et al 17 70.9% at one year. In a meta-analysis consisting of 14 studies, Patel et al 12 came up with a 63.4% primary patency rate for PTFE-covered self-expandable stent-graft at five years.…”
Section: Discussionmentioning
confidence: 99%